Proceedings of the First International Workshop on Process Algebra and Coordination (PACO 2011, Reykjavik, Iceland, June 9, 2011) - Aceto, L; Mousavi, M Mohammad Reza (Elsevier, 2011)
Process algebra provides abstract and rigorous means for studying communicating concurrent systems. Coordination languages also provide abstract means for the specifying and programming communication of components. Hence, the two fields seem to have very much in common and the link between these two research areas have been established formally by means of several translations, mainly from coordination languages to process algebras. There have also been proposals of process algebras whose communication policy is inspired by the one underlying coordination languages. The aim of this workshop was to push the state of the art in the study of the connections between process algebra and coordination languages by bringing together experts as well as young researchers from the two fields to communicate their ideas and findings. It includes both contributed and invited papers that have been presented during the one day meeting on Process Algebra and Coordination (PACO 2011) which took place on June 9, 2011 in Reykjavik, Iceland.